Youth background and financial wellbeing - Abdullah, Haslinda; Ortega, Adriana; Ismail, Ismi Arif (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
The study aimed to (a) assess the difference based on ethnicity and age in financial well-being among Malaysian youth. Methods: Data were obtained from 2011 Youth Index (MYI’ 2011). The MYI’ 2011 provided indicators of the overall health and well-being status of Malaysian youth and was designed to identify potential issues affecting young people’s quality of life and well-being. For this study authors used financial well-being indicators from MYI’2011. Sample: The sample consisted of 5720 young Malaysians between the age range of 18 and 40 years old. Majority of the sample (68.3%) were Malay, 14.2% were Chinese, 7% were Indians and the remaining 10.5% were east Malaysians and other ethnicities. Majority of participants lived in urban areas (56%) and rural areas (46%), while a very small portion of the sample resided in Felda/Felcra communities. Results: There were significant differences regarding financial security indicators among Malaysian youth based on youth’s ethnicity and age groups. Financial security was also found to be significantly associated with security. Implications: The findings indicate that young people’s financial wellbeing might be an aspect that could be enhanced through tailored youth programs.